Zirconium oxide modified carrier, condensation catalyst, preparation methods and applications of zirconium oxide modified carrier and condensation catalyst, and methyl acrylate synthesis method
By using zirconia modified support, the problems of low catalyst stability and conversion rate are solved, and efficient methyl acrylate synthesis is achieved, and the catalyst operates stably for a long time at high temperatures.
Patent Information
- Application Number
- CN202410100416.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-24
- Publication Date
- 2025-07-25
AI Technical Summary
In the prior art, the catalytic one-way conversion rate of methyl acrylate is not high and the catalyst stability is poor, making it difficult to achieve industrial production.
Zirconium oxide (ZrO2) modified support is used to modify the support with amorphous ZrO2 before loading the active component, and control the calcination conditions to transform the ZrO2 on the catalyst surface into an orthogonal square phase, thereby improving the hydrothermal stability and activation ability of the catalyst.
The reaction conversion and selectivity of the catalyst are improved, and the catalyst operates stably for a long period of time at high temperatures. It is suitable for condensation reactions such as synthesis of methyl acrylate, achieving continuous and stable operation for more than 10 days.
Smart Images

Figure BDA0004680097920000071
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysts, and specifically relates to a zirconia-modified carrier and its preparation method and application, a condensation catalyst and its preparation method and application, and a method for synthesizing methyl acrylate. Background Art
[0002] In the prior art, the preparation methods of acrylic acid and its esters mainly include propylene oxidation method, acrylonitrile hydrolysis method, ketene method, propane oxidation method, and methyl formate method to solve the problem of greatly excessive production capacity of methyl acetate in China. However, the foregoing methods have problems such as high energy consumption, low product yield, and serious environmental pollution. Currently, based on the mature α-MMA process proposed by Lucite company, a method using methyl acetate and formaldehyde as raw materials and a new catalyst for synthesizing methyl acrylate has been proposed. Although the problems of short single-pass life of the catalyst, easy carbon deposition, and frequent regeneration have been solved, the comprehensive improvement of yield, selectivity, and catalyst stability still cannot be achieved, and it is difficult to realize industrial production.
[0003] CN103638956A discloses a catalyst for synthesizing methyl acrylate from trioxymethylene or paraformaldehyde, acetic acid, and aqueous acetic acid solution, and its preparation and application methods. It is characterized in that phosphoric acid, ammonium metavanadate, and an alkali metal salt are selected as the sources of active components, and the alkali metal salt is selected from any one or a mixture of two or more of cesium nitrate, cesium carbonate, potassium hydroxide, sodium hydroxide, magnesium carbonate, calcium carbonate, and barium carbonate. Among them, the loading amount of vanadium is 5-30 wt%, preferably 8%-26 wt%, and further preferably 10-25 wt%; the molar ratio of phosphorus to vanadium is 0.5-4, and the alkali metal atoms account for 1%-5% of the total mass of the catalyst. Its disadvantage is that the selectivity of methyl acrylate can only reach 55%. Summary of the Invention
[0004] One of the technical problems to be solved by the present invention is the problems such as low catalytic single-pass conversion rate and poor catalyst stability in the industrial synthesis of methyl acrylate by aldol condensation reaction. A zirconia (ZrO2)-modified carrier is provided. The modified carrier includes ZrO2 and a carrier substance; the ZrO2 includes amorphous ZrO2. When the condensation aldol condensation catalyst prepared from the ZrO2-modified carrier is used in the synthesis of alkyl acrylate, such as the method of condensing formaldehyde and methyl acetate to synthesize methyl acrylate, it has the effects of high reaction conversion rate, high selectivity, and strong high-temperature hydrothermal stability of the catalyst.
[0005] The research of the present invention finds that ZrO2 can be divided into amorphous phase and crystalline phase, and the crystalline phase is further divided into orthorhombic phase, tetragonal phase and cubic phase. Since the amorphous phase has strong acidity and high acid density, the carrier can be modified with amorphous ZrO2 before loading the active component source. When loading the active component source, the precursor of the active component source can be highly dispersed and loaded on the surface of the carrier (ZrO2 with strong acidity and high acid density has strong adsorption ability for basic precursors), and it is not easy to agglomerate and grow during the drying and calcination processes, resulting in a decrease in activity. During calcination, by controlling the calcination conditions, the ZrO2 on the catalyst surface is in-situ transformed into orthorhombic phase. Compared with amorphous ZrO2, orthorhombic ZrO2 has weaker acidity, so the basicity of the active phase on the catalyst surface becomes stronger, and the activation ability is enhanced. At the same time, the loading of ZrO2 can effectively improve the hydrothermal stability of the catalyst.
[0006] To achieve the above object, on the one hand, the present invention provides a ZrO2 modified carrier, and the modified carrier includes ZrO2 and a carrier material; the ZrO2 includes amorphous ZrO2.
[0007] On the second aspect, the present invention provides a preparation method of the ZrO2 modified carrier described in the present invention, and the preparation method includes: performing a first impregnation on a ZrO2 source and a carrier material, and calcining at 300 - 350 °C.
[0008] On the third aspect, the present invention provides the application of the ZrO2 modified carrier described in the present invention and the preparation method of the ZrO2 modified carrier described in the present invention in the preparation of a condensation catalyst.
[0009] On the fourth aspect, the present invention provides a condensation catalyst, and the condensation catalyst includes a condensation active component and a carrier, the carrier contains the ZrO2 modified carrier described in the present invention, and the ZrO2 in the catalyst includes monoclinic ZrO2.
[0010] On the fifth aspect, the present invention provides a preparation method of the condensation catalyst described in the present invention, and the method includes: preparing a modified carrier according to the method described in the present invention, performing a second impregnation on a condensation active component source and the modified carrier, and calcining at 500 - 550 °C.
[0011] On the sixth aspect, the present invention provides the application of the condensation catalyst described in the present invention in the synthesis of alkyl acrylate, and the alkyl acrylate is selected from one or more of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate.
[0012] On the seventh aspect, the present invention provides a method for synthesizing methyl acrylate, and the method includes: contacting a raw material containing methyl acetate, formaldehyde, and methanol with a catalyst for reaction; the catalyst includes the condensation catalyst described in the present invention or a condensation catalyst prepared according to the method described in the present invention.
[0013] By the above technical solution, the present invention has the following beneficial effects:
[0014] Before loading the active component source, the carrier is modified with amorphous ZrO2. When loading the active component source, the precursor of the active component source can be highly dispersed and loaded on the surface of the carrier (ZrO2 with strong acidity and high acid density has a strong adsorption capacity for basic precursors), and it is not easy to aggregate and grow during the drying and calcination processes, resulting in a decrease in activity. During calcination, by controlling the calcination conditions, the ZrO2 on the catalyst surface is in-situ transformed into orthorhombic phase. Compared with amorphous ZrO2, orthorhombic ZrO2 has weaker acidity, so the basicity of the active phase on the catalyst surface becomes stronger, and the activation ability is enhanced. At the same time, the loading of ZrO2 can effectively improve the hydrothermal stability of the catalyst. Specific Embodiments
[0015] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.
[0016] The present invention provides a zirconia (ZrO2) modified carrier, and the modified carrier includes ZrO2 and a carrier material; the ZrO2 includes amorphous ZrO2.
[0017] The ZrO2 modified carrier of the present invention has the advantages of ensuring high dispersion of active centers while maintaining high catalytic activity and good high-temperature hydrothermal stability. The condensation catalyst prepared from the ZrO2 modified carrier of the present invention has the effects of high reaction conversion rate, high selectivity, and strong high-temperature hydrothermal stability of the catalyst, which is beneficial to the long-term stable operation of the condensation reaction. In the method for condensation reaction such as the condensation synthesis of methyl acrylate, it has achieved continuous stable operation for more than 10 days without obvious deactivation of the catalyst.
[0018] According to a particularly preferred embodiment of the present invention, in the ZrO2 modified carrier, the amorphous ZrO2 accounts for ≥90% of the total amount of ZrO2, and preferably the amorphous ZrO2 accounts for 95-99% of the total amount of ZrO2. By adopting the foregoing preferred embodiment, the dispersion degree of the alkali metal oxide on the carrier surface can be further improved.
[0019] In the present invention, there is no special requirement for the content of ZrO2 based on the total weight of the modified support. According to a particularly preferred embodiment of the present invention, the content of ZrO2 is 0.001 - 30 wt%, preferably 0.01 - 10 wt%, more preferably 0.1 - 5 wt%, and further preferably 1 - 3 wt%. By adopting the aforementioned preferred embodiments, the dispersion degree, base strength, and high-temperature hydrothermal stability of the supported active centers can be further improved.
[0020] According to a particularly preferred embodiment of the present invention, based on the total weight of the modified support, the modified support contains 0.1 - 10 wt% ZrO2 and 90 - 99.9 wt% support material.
[0021] In the present invention, the support material can be a conventional choice in the art. By way of example, but not limiting the scope of the present invention thereby, the support is selected from one or more of SiO2, Al2O3, and activated carbon, and is preferably SiO2.
[0022] ZrO2-modified supports having the aforementioned characteristics can all be used in the present invention, and there is no special requirement for their preparation method. For the present invention, a preparation method of a ZrO2-modified support is provided. This preparation method includes: performing a first impregnation on a ZrO2 source and a support source, and calcining at 300 - 350 °C; in the present invention, there is no special requirement for the calcination time, generally 2 - 20 h, and it can be adjusted according to actual operations. The preferred calcination time is 5 - 8 h. In the examples, 5 h, 6 h, and 8 h are used for illustrative purposes, but not limiting the scope of the present invention thereby; after the precursor ZrO2 source decomposes, the obtained ZrO2 is in an amorphous state, and preferably the amorphous ZrO2 accounts for ≥90% of the total amount of ZrO2.
[0023] According to a preferred embodiment of the present invention, the ZrO2 source is selected from one or more of ZrOCl2, ZrCl4, ZrO(NO3)2, and Zr(NO3)4. In the examples, ZrOCl2 is used to illustrate the advantages of the present invention by way of example.
[0024] According to a preferred embodiment of the present invention, the support source is selected from one or more of SiO2, Al2O3, and activated carbon.
[0025] According to a preferred embodiment of the present invention, the conditions for the first impregnation include a solid-liquid volume ratio of 0.1 - 3.
[0026] According to a preferred embodiment of the present invention, the first impregnation solution contains an organic substance. Based on the total weight of the first impregnation solution, the organic substance is 0.01 - 2 wt%. In the examples, 1 wt% is used for illustrative purposes, but not limiting the scope of the present invention thereby.
[0027] According to a preferred embodiment of the present invention, the organic substance is selected from one or more of polyvinyl alcohol, polyethylene glycol, and oleic acid. The average molecular weight of polyvinyl alcohol is 50,000 - 100,000; the average molecular weight of polyethylene glycol is 200 - 9,500. Preferably, the organic substance is selected from polyethylene glycol and / or oleic acid. More preferably, the organic substance is a mixture of polyethylene glycol and oleic acid, and the content of any one of polyethylene glycol and oleic acid in the mixture is not less than 10% by weight, preferably the content of any one is 20 - 80% by weight.
[0028] In the present invention, there is no special requirement for the impregnation method. For illustrative purposes only, but without limiting the scope of the present invention thereby. According to a particularly preferred embodiment of the present invention, methods such as equal-volume impregnation, excess impregnation, or shaped blending are used to introduce the Zr precursor, and the calcination temperature of the modified support is controlled at 300 - 350 °C to ensure that the ZrO2 obtained after the decomposition of the precursor is in an amorphous state. Preferably, the amorphous ZrO2 accounts for ≥90% of the total amount of ZrO2.
[0029] In the present invention, there is no special requirement for the shape of the carrier. Those skilled in the art can select according to actual operations. In the examples of the present invention, 2-mm clover is used for illustrative purposes only, but without limiting the scope of the present invention thereby.
[0030] In the preparation step of the support in the present invention, after the impregnation step and before the calcination step, the support also needs to be dried. The drying conditions are well-known to those skilled in the art. For illustrative purposes only, but without limiting the scope of the present invention thereby. For example, the drying temperature is 100 - 120 °C, and the time is 8 - 24 h. The example of drying in an oven at 110 °C for 12 h is used to illustrate the advantages of the present invention, but the scope of the present invention cannot be limited thereby.
[0031] The present invention provides the application of the ZrO2-modified support described in the present invention or the preparation method of the ZrO2-modified support described in the present invention in the preparation of a catalyst, preferably in the preparation of a condensation catalyst.
[0032] The present invention provides a condensation catalyst. The condensation catalyst includes a condensation active component and a support. The support contains the ZrO2-modified support described in the present invention. The ZrO2 in the catalyst includes monoclinic ZrO2.
[0033] In the present invention, the range of selection of the condensation active component elements is relatively wide. For illustrative purposes only, but without limiting the scope of the present invention thereby. According to a particularly preferred embodiment of the present invention, the source elements of the condensation active component are selected from at least one of sodium, potassium, rubidium, and cesium. In the examples of the present invention, for illustrative purposes, cesium is provided in the form of cesium oxide. By adopting the aforementioned preferred embodiment, the base strength of cesium oxide in the finished catalyst can be further improved, thereby improving the activity and selectivity of the catalyst.
[0034] In the present invention, calculated on the total weight of the catalyst and in terms of oxide, the content of the condensation active component has a relatively wide optional range. According to a preferred embodiment of the present invention, the content of the source of the condensation active component is 0.5 - 50 wt%. By adopting the aforementioned preferred embodiment, the conversion rate, selectivity and long-term stability of the reaction can be further improved.
[0035] The present invention provides a method for preparing the condensation catalyst described in the present invention. The method includes: preparing a modified support according to the method described in the present invention, performing a second impregnation of the source of the condensation active component and the modified support, and calcining at 500 - 550 °C.
[0036] By way of illustration but not limitation of the scope of the present invention, the source of the condensation active component and the modified support of the present invention can be impregnated by equal volume or excess impregnation. Here, mainly by controlling the catalyst calcination temperature at 500 - 550 °C, the amorphous ZrO2 in the modified support is in-situ transformed into the monoclinic phase. In the present invention, the catalyst calcination time is well-known to those skilled in the art and can be adjusted according to actual operations. The preferred calcination time is 5 - 8 h. In the examples, 5 h, 6 h, and 8 h are used for illustration but not limitation of the scope of the present invention.
[0037] In the present invention, in the preparation steps of the catalyst, after the impregnation step and before the calcination step, the catalyst also needs to be dried. The drying conditions are well-known to those skilled in the art. For example, the drying temperature is 100 - 120 °C and the time is 8 - 24 h. The examples use drying at 110 °C in an oven for 12 h to exemplify the advantages of the present invention, but the scope of the present invention cannot be limited thereby.
[0038] The present invention provides the application of the condensation catalyst described in the present invention in the synthesis of alkyl acrylates. According to a preferred embodiment of the present invention, the alkyl acrylates are selected from one or more of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate.
[0039] The present invention provides a method for synthesizing methyl acrylate. The method includes: contacting a raw material containing methyl acetate, formaldehyde, and methanol with a catalyst; the catalyst includes the condensation catalyst described in the present invention or a condensation catalyst prepared according to the method described in the present invention.
[0040]
[0041] In the present invention, there are no special requirements for the molar ratio of methyl acetate to formaldehyde. According to a preferred embodiment of the present invention, the molar ratio of methyl acetate to formaldehyde is 0.1 - 50. In the examples, the molar ratio of methyl acetate to formaldehyde is exemplified as 0.1, but this does not limit the scope of the present invention.
[0042] In the present invention, there are no special requirements for the proportion of methanol in the total raw materials. According to a preferred embodiment of the present invention, the proportion of methanol in the total raw materials is 5 - 50 wt%. In the examples, the proportion of methanol in the total raw materials is exemplified as 6 wt%, but this does not limit the scope of the present invention.
[0043] In the present invention, methanol, as a solvent substance that does not participate in the reaction, is well-known to those skilled in the art.
[0044] In the present invention, there are no special requirements for the conditions of the contact reaction. The following is an exemplary description, but this does not limit the scope of the present invention.
[0045] According to a preferred embodiment of the present invention, the contact temperature is 200 - 500 °C, preferably 250 - 450 °C. In the examples, the contact temperature is exemplified as 320 °C, but this does not limit the scope of the present invention.
[0046] According to a preferred embodiment of the present invention, the contact pressure is 0 - 5 Mpa, preferably 0.05 - 2.0 Mpa. In the examples, the contact pressure is exemplified as 0.2 Mpa, but this does not limit the scope of the present invention.
[0047] According to a preferred embodiment of the present invention, the volume hourly space velocity of the contact feed gas is 300 - 1800 h -1 , and in the examples, the volume hourly space velocity of the contact feed gas is exemplified as 0.6 h -1 for exemplary illustration, but this does not limit the scope of the present invention.
[0048] In the present invention, the catalyst composition is based on the composition calculated from the feedstock.
[0049] In the present invention, the conversion rate of methyl acetate and the selectivity of methyl acrylate in the examples are well-known to those skilled in the art and can be referred to the prior art. Therefore, they are not elaborated herein.
[0050] The present invention will be described in detail below through examples.
[0051] Example 1
[0052] (1) Preparation of modified SiO2 support: Using the equal-volume impregnation method, zirconium oxychloride was used as the precursor to impregnate and load the SiO2 support (2 mm clover-shaped). It was dried in an oven at 110 °C for 12 h and then transferred to a muffle furnace for calcination at 350 °C for 6 h to obtain the modified SiO2 support (the amorphous ZrO2 accounts for 99 wt% of the total ZrO2, and the ZrO2 loading is 1 wt%).
[0053] (2) Preparation of Cs2O catalyst with a loading of 5 wt%: Using the equal-volume impregnation method, CsNO3 was used as the precursor to impregnate and load the above-mentioned modified support. It was dried in an oven at 110 °C for 12 h and then transferred to a muffle furnace for calcination at 550 °C for 6 h to obtain the finished catalyst, and the orthorhombic ZrO2 accounts for 98% of the total ZrO2.
[0054] (3) Take 5 g of the catalyst and load it into a reactor (inner diameter 16 mm, length 1500 mm). After purging with N2 three times, the temperature was raised to 320 °C and the pressure was adjusted to 0.2 MPa. With the total mass space velocity of methyl acetate, formaldehyde, and methanol being 0.6 h -1 The reaction raw materials were introduced (the composition of the reaction raw materials by weight is formaldehyde∶methyl acetate∶methanol = 1:10:5). Samples were taken, internal standard toluene was added, and the contents of each component in the reaction mixture were measured by gas chromatography. The conversion rate of methyl acetate was calculated to be 18.6%, and the selectivity of methyl acrylate was 93.5%. After running for 10 days, the conversion rate of methyl acetate was 17.8%, and the selectivity of methyl acrylate was 92.8%.
[0055] Example 2
[0056] (1) Preparation of modified SiO2 support: Using the equal-volume impregnation method, zirconium oxychloride was used as the precursor to impregnate and load the SiO2 support (2 mm clover-shaped). It was dried in an oven at 110 °C for 12 h and then transferred to a muffle furnace for calcination at 300 °C for 8 h to obtain the modified SiO2 support (the amorphous ZrO2 accounts for 95 wt% of the total ZrO2, and the ZrO2 loading is 1 wt%).
[0057] (2) Preparation of Cs2O catalyst with a loading of 3 wt%: Using the equal-volume impregnation method, CsNO3 was used as the precursor to impregnate and load the above-mentioned modified support. It was dried in an oven at 110 °C for 12 h and then transferred to a muffle furnace for calcination at 500 °C for 5 h to obtain the finished catalyst, and the orthorhombic ZrO2 accounts for 96% of the total ZrO2.
[0058] Using the same evaluation method as in step (3) of Example 1: The conversion rate of methyl acetate was 17.3%, and the selectivity of methyl acrylate was 92.1%. After running for 10 days, the conversion rate of methyl acetate was 16.8%, and the selectivity of methyl acrylate was 92.4%.
[0059] Example 3
[0060] (1) Preparation of modified SiO2 support: Using the equal-volume impregnation method, zirconium oxychloride was used as the precursor to impregnate and load the SiO2 support (2mm clover), dried in an oven at 110°C for 12h, transferred to a muffle furnace and calcined at 320°C for 5 hours to obtain the modified SiO2 support (the amorphous ZrO2 accounts for 97 wt% of the total ZrO2, and the ZrO2 loading is 1.5 wt%).
[0061] (2) Preparation of Cs2O catalyst with a loading of 8 wt%: Using the equal-volume impregnation method, CsNO3 was used as the precursor to impregnate and load the above modified support, dried in an oven at 110°C for 12h, transferred to a muffle furnace and calcined at 530°C for 8 hours to obtain the finished catalyst, and the orthorhombic ZrO2 accounts for 97% of the total ZrO2.
[0062] Using the same evaluation method as in step (3) of Example 1: The conversion rate of methyl acetate was 17.8%, the selectivity of methyl acrylate was 92.1%. After running for 10 days, the conversion rate of methyl acetate was 17.2%, and the selectivity of methyl acrylate was 91.6%.
[0063] Example 4
[0064] All are the same as in Example 1, except that: In step (2), a Rb2O catalyst with a loading of 5 wt% was prepared: Using the equal-volume impregnation method, RbNO3 was used as the precursor to impregnate and load the above modified support, dried in an oven at 110°C for 12h, transferred to a muffle furnace and calcined at 550°C for 6 hours to obtain the finished catalyst, and the orthorhombic ZrO2 accounts for 98% of the total ZrO2.
[0065] Using the same evaluation method as in step (3) of Example 1: The conversion rate of methyl acetate was 16.8%, the selectivity of methyl acrylate was 92.4%. After running for 10 days, the conversion rate of methyl acetate was 15.7%, and the selectivity of methyl acrylate was 92.8%.
[0066] Example 5
[0067] All conditions are the same as in Example 1, except that: In step (1), the modified SiO2 support was prepared: Using the equal-volume impregnation method, zirconium oxychloride was used as the precursor to impregnate and load the SiO2 support (2mm clover) in polyvinyl alcohol (average molecular weight of 80,000) (polyvinyl alcohol is 1 wt% of the total impregnation solution), dried in an oven at 110°C for 12h, transferred to a muffle furnace and calcined at 350°C for 6 hours to obtain the modified SiO2 support (the amorphous ZrO2 accounts for 99 wt% of the total ZrO2, and the ZrO2 loading is 1 wt%).
[0068] The catalyst was prepared in the same manner as in Example 1. Among them, in the catalyst, orthorhombic ZrO2 accounted for 99% of the total ZrO2.
[0069] The same evaluation method as in step (3) of Example 1 was adopted: the conversion rate of methyl acetate was 19.1%, the selectivity of methyl acrylate was 93.6%. After running for 10 days, the conversion rate of methyl acetate was 18.5%, and the selectivity of methyl acrylate was 93.5%.
[0070] Example 6
[0071] According to the method of Example 5, the difference is that polyethylene glycol with an average molecular weight of 7000 was used instead of polyvinyl alcohol (average molecular weight of 80000).
[0072] The same evaluation method as in step (3) of Example 1 was adopted: the conversion rate of methyl acetate was 19.5%, the selectivity of methyl acrylate was 93.8%. After running for 10 days, the conversion rate of methyl acetate was 18.9%, and the selectivity of methyl acrylate was 94.1%.
[0073] Example 7
[0074] According to the method of Example 6, the difference is that a mixture of polyethylene glycol with an average molecular weight of 7000 and oleic acid (mass ratio of the two is 1:1) was used instead of polyethylene glycol, and the total amount of organic substances used remained unchanged.
[0075] The same evaluation method as in step (3) of Example 1 was adopted: the conversion rate of methyl acetate was 19.8%, the selectivity of methyl acrylate was 94.1%. After running for 10 days, the conversion rate of methyl acetate was 19.5%, and the selectivity of methyl acrylate was 94.5%.
[0076] Comparative Example 1
[0077] All conditions were the same as in Example 1, the difference is: in step (2), the calcination condition of the catalyst was calcined at 450 °C for 6 hours.
[0078] The same evaluation method as in step (3) of Example 1 was adopted: the conversion rate of methyl acetate was 15.2%, the selectivity of methyl acrylate was 87.8%. After running for 10 days, the conversion rate of methyl acetate was 14.6%, and the selectivity of methyl acrylate was 88.3%.
[0079] Comparative Example 2
[0080] All conditions were the same as in Example 1, the difference is: in step (2), the calcination condition of the catalyst was calcined at 600 °C for 6 hours.
[0081] The same evaluation method as in step (3) of Example 1 was adopted: the conversion rate of methyl acetate was 13.8%, and the selectivity of methyl acrylate was 85.2%. After running for 10 days, the conversion rate of methyl acetate was 11.2%, and the selectivity of methyl acrylate was 86.1%.
[0082] Comparative Example 3
[0083] All conditions were the same as in Example 1, except that: in step (1), the prepared modified SiO2 support was transferred to a muffle furnace and calcined at 250 °C for 6 hours.
[0084] The same evaluation method as in step (3) of Example 1 was adopted: the conversion rate of methyl acetate was 12.1%, and the selectivity of methyl acrylate was 83.6%. After running for 10 days, the conversion rate of methyl acetate was 10.3%, and the selectivity of methyl acrylate was 82.8%.
[0085] Comparative Example 4
[0086] All conditions were the same as in Example 1, except that: in step (1), the prepared modified SiO2 support was transferred to a muffle furnace and calcined at 400 °C for 6 hours.
[0087] The same evaluation method as in step (3) of Example 1 was adopted: the conversion rate of methyl acetate was 14.3%, and the selectivity of methyl acrylate was 86.1%. After running for 10 days, the conversion rate of methyl acetate was 12.2%, and the selectivity of methyl acrylate was 84.7%.
[0088] Comparative Example 5
[0089] All conditions were the same as in Example 1, except that: zirconium oxychloride was not used to modify the support, that is, step (1) was not included.
[0090] The same evaluation method as in step (3) of Example 1 was adopted: the conversion rate of methyl acetate was 10.2%, and the selectivity of methyl acrylate was 81.3%. After running for 10 days, the conversion rate of methyl acetate was 7.6%, and the selectivity of methyl acrylate was 80.2%.
[0091] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.
Claims
1. A zirconia-modified support, characterized in that, The modified support includes ZrO2 and a support material; the ZrO2 includes amorphous ZrO2.
2. The modified support according to claim 1, wherein the amorphous ZrO2 accounts for ≥90% of the total amount of ZrO2, and preferably the amorphous ZrO2 accounts for 95-99% of the total amount of ZrO2; and / or calculated based on the total weight of the modified support, the content of ZrO2 is 0.001-30 wt%, preferably 0.01-10 wt%, more preferably 0.1-5 wt%, and further preferably 1-3 wt%; preferably, calculated based on the total weight of the modified support, the modified support contains 0.1-10 wt% ZrO2 and 90-99.9 wt% support material; and / or the support material is selected from one or more of SiO2, Al2O3, and activated carbon, and preferably is SiO2.
3. A method for preparing the modified carrier according to claim 1 or 2, characterized in that, The preparation method includes: performing a first impregnation on a ZrO2 source and a support source, and calcining at 300-350 °C; Preferably, the calcination time is 5-8 h; Preferably, the ZrO2 source is selected from one or more of ZrOCl2, ZrCl4, ZrO(NO3)2, and Zr(NO3)4; Preferably, the support source is selected from one or more of SiO2, Al2O3, and activated carbon; Preferably, the conditions for the first impregnation include a solid-liquid volume ratio of 0.1-3; Preferably, the first impregnation solution contains an organic substance, and calculated based on the total weight of the first impregnation solution, the content of the organic substance is 0.01-2 wt%; Preferably, the organic substance is selected from one or more of polyvinyl alcohol, polyethylene glycol, and oleic acid; The average molecular weight of the polyvinyl alcohol is 50000-100000; The average molecular weight of the polyethylene glycol is 200-9500; Preferably, the organic substance is selected from polyethylene glycol and / or oleic acid, and more preferably the organic substance is a mixture of polyethylene glycol and oleic acid, and the content of any one of polyethylene glycol and oleic acid in the mixture is not less than 10% by weight, and preferably the content of any one is 20-80% by weight.
4. The application of the ZrO2 modified support according to claim 1 or 2 or the preparation method of the ZrO2 modified support according to claim 3 in the preparation of a catalyst, preferably in the preparation of a condensation catalyst.
5. A condensation catalyst, characterized in that, The condensation catalyst includes a condensation active component and a support, the support includes the ZrO2 modified support according to claim 1 or 2, and the ZrO2 in the catalyst includes monoclinic ZrO2; Preferably, calculated based on the total weight of the catalyst and in terms of oxides, the content of the condensation active component is 0.5-50 wt%, preferably 1-10 wt%.
6. The condensation catalyst according to claim 5, wherein the condensation active component element is selected from at least one of sodium, potassium, rubidium, and cesium, and preferably is cesium; and / or the monoclinic ZrO2 in the catalyst accounts for ≥90% of the total amount of ZrO2.
7. A method for preparing the condensation catalyst according to claim 5 or 6, characterized in that, The method includes: preparing a modified support according to the method described in claim 3, performing a second impregnation on a condensation active component source and the modified support, and calcining at 500-550 °C; Preferably, the calcination time is 5-8 h.
8. Use of the condensation catalyst according to claim 7 in the synthesis of alkyl acrylate. Preferably, the alkyl acrylate is selected from one or more of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate and butyl methacrylate.
9. A method for synthesizing methyl acrylate, characterized in that, The method comprises: contacting a raw material containing methyl acetate, formaldehyde and methanol with a catalyst for reaction; The catalyst comprises the condensation catalyst according to claim 5 or 6 or the condensation catalyst prepared by the method according to claim 7.
10. According to the method of claim 9, wherein The molar ratio of methyl acetate to formaldehyde is 0.1 - 50; and / or The proportion of methanol in the total raw material is 5 - 50 wt%; and / or The conditions of the contacting reaction include: The temperature is 200 - 500 °C, preferably 250 - 450 °C; and / or The pressure is 0 - 5 Mpa, preferably 0.05 - 2.0 Mpa; and / or The volumetric space velocity of the feed gas is 300 - 1800 h -1 .
Citation Information
Patent Citations
Catalyst for synthesizing methyl acrylate by trioxymethylene or paraformaldehyde and acetic acid and acetic acid aqueous solution, its preparation and its application method
CN103638956A